Can Good Governance Lower Financial Intermediation Costs? - Jarmuzek, Mariusz (IMF Working Papers; Working Paper, 2018)
This paper argues that better governance practices can reduce the costs, risks and uncertainty of financial intermediation. Our sample covers high-, middle- and low-income countries before and after the global financial crisis (GFC). We find that net interest margins of banks are lower if various governance indicators are better. More cross-border lending also appears conducive to lower intermediation costs, while the level of capital market development is not significant. The GFC seems not to have had a strong impact except via credit risk. Finally, we estimate the size of potential gains from improved governance.